Fighting Women of Kabuki Theater and the Legacy of Women's Japanese Martial Arts - Deborah Klens-Bigman (Universidad de León, 2012)
The fighting woman character has been a staple of Japan's kabuki theater almost since its inception. Audiences accepted these characters, especially fighting women of the samurai class, as part of the depiction of Edo period (1603-1868) life. This paper explores several of these characters and suggests that they help form the legacy of women's practice of martial arts today.